Treatment of Spinal Metastases with Epidural Cord Compression through Corpectomy and Reconstruction via the Traditional Open Approach versus the Mini-Open Approach: A Multicenter Retrospective Study. (2nd May 2019) - Zhou, Xi; Cui, Haomin; He, Yu; Qiu, Guixing; Zhou, Dongsheng; Liu, Yong
Abstract : Patients with metastatic epidural spinal cord compression (MESCC) often need surgical intervention due to pain, neurological deficits, and spinal instability. Spinal disease is commonly treated via the minimally invasive mini-open approach. However, few studies have evaluated MESCC treatment via mini-open approach. The present study compared the traditional open approach versus the mini-open approach for thoracolumbar MESCC. A cohort of 209 consecutive patients who were diagnosed with thoracolumbar metastases and underwent corpectomy and polymethylmethacrylate reconstruction from 2010 to 2016 was retrospectively identified. Traditional open surgery was performed in 113 patients (open group; mean age 57.7 years), while 96 patients underwent mini-open surgery (mini-open group; mean age 54.3 years). Patients were followed up for 24 months or until death. The baseline characteristics of both groups were similar. The most common origin of the primary lesion was the lung (37.3%), hematological system (22.0%), and kidney (15.8%). Surgery effectively achieved pain relief, restored neurological function, and improved quality of life in both groups. The mini-open group was superior to the open group regarding estimated blood loss, blood transfusion, hospital stay, complications, and pain score. While the mini-open group had a longer operation time than the open group, the two groups had similar improvements in the Frankel grade and Karnofsky functional score. The 30-day mortality rate tended to be higher in the open group (5.3%) than the mini-open group (2.1%) without significance. The 24-month survival rate was similar in both groups (26.5% versus 26.0%). In conclusion, surgery improved pain, function, and quality of life in patients with MESCC. The mini-open approach resulted in less estimated blood loos, less blood transfusion, and shorter hospitalization than the traditional open approach, while both methods had similar mortality and morbidity rates. Thus, the mini-open approach may be more beneficial than the traditional approach for MESCC.